Effects of Amnion Lyophilization Sterile Radiation against the Number of Osteoblasts and Osteocytes in Nonunion Fractures: An Experimental Research Study - Fauzi, Ahmad; Alvarino, Alvarino; Yanwirasti, Yanwirasti; Sahputra, Roni Eka; Suharmanto, Suharmanto (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: This study used an experimental posttest-only control group design that involved white rats of the Sprague Dawley strain. Methods: The samples used were 8-week-old rats, weighing 250–350 grams of the male sex. The study was conducted on five groups of rats with a total of seven rats per group. Results: The mean value of osteocytes in the control group was 00.00 ± 00.00 and in the ALSR group it was 87.14 ± 44.85. The mean value of osteoblasts in the control group was 50.06 ± 5.76 and in the ALSR group it was 283.63 ± 22.86. This study showed that there were differences in the number of osteocytes and osteoblasts in the two groups. Conclusion: The study reported that the ALSR group had significantly different numbers of osteoblasts and osteocytes than the control group.